The Intergenerational Correlation of Employment: Is There a Role for Work Culture? - Gabriela Galassi; David Koll; Lukas Mayr (Institute of Labor Economics (IZA), 2019)
We document a substantial positive correlation of employment status between mothers and their children in the United States, linking data from the National Longitudinal Survey of Youth 1979 (NLSY79) and the NLSY79 Children and Young Adults. After controlling for ability, education, and wealth, a one-year increase in a mother's employment is associated with six weeks more employment of her child on average. The intergenerational transmission of maternal employment is stronger to daughters than to sons, and it is higher for low-educated and low-income mothers. Potential mechanisms we were able to rule out include networks, occupation-specific human capital and conditions within the local labor market. By contrast, we provide suggestive evidence for a role-model channel through which labor force participation is transmitted.
Keywords: E24; J21; J22; J62; 330; intergenerational transmission; preferences for work; female employment